A review of unloading-induced fault instability - Wu, Wei (2021)
Induced seismicity associated with underground space creation and resource extraction has become a matter of global concern, but our ability to predict and mitigate the anthropogenic geohazards is still woefully inadequate. This review provides an overview of unloadinginduced seismicity and highlights the mechanisms behind fault instability from a view of rock mechanics. Based on numerous fault instability cases, reduction and rotation of in situ stresses on pre-existing faults are possible causes of excavation-induced seismicity. Fault instability during resource extraction is related to many geological and operational factors, including mining depth, pore pressure, stress distribution, and production rate. Most of these cases can be explained by the Mohr–Coulomb failure criterion, and some exceptional cases could offer us new clues to improve the understanding of the mechanisms behind and the ability to predict and mitigate the induced seismic events. The current challenges include how to control remote triggering of fault instability and how to manage unseen threat of undetected faults. Emerging technologies, such as data analytics and machine learning, combining with physical models could be the next frontier for fault instability research